Pengaruh Diabetes Self-Management Education (DSME) Melalui E-Booklet Tehadap Efikasi Diri pada Pasien Diabetes Mellitus di RSUD Kajen Pekalongan - Lia Leonita; Emilia Puspitasari; Rahayu Winarti (Journal of Health, Medical, and Psychological Studies, 2026)
Diabetes mellitus (DM) is a chronic metabolic disorder with a steadily increasing prevalence at both global and national levels. This condition poses a high risk of severe complications, including cardiovascular disease, renal failure, and neuropathy. Effective management of DM requires active patient participation through Diabetes Self-Management (DSM), which is strongly influenced by self-efficacy. However, many patients still exhibit low self-efficacy, highlighting the need for educational interventions such as Diabetes Self-Management Education (DSME), including those delivered through digital media like e-booklets. This study aims to examine the effect of DSME delivered via e-booklets on the self-efficacy of DM patients at RSUD Kajen Pekalongan. The study employed a quantitative approach with a quasi-experimental one-group pretest–posttest design without a control group. The population consisted of hospitalized DM patients, with an average of 92 patients per month, and a sample of 92 respondents selected using purposive sampling. Data were collected using the Diabetes Management Self-Efficacy Scale questionnaire and analyzed through frequency distribution and the Wilcoxon test. The results indicate that 90% of respondents had low self-efficacy prior to the intervention, which increased to 66.9% in the moderate category following the intervention. Statistical analysis revealed a significant effect (p = 0.000), confirming that e-booklet-based DSME effectively enhances self-efficacy among patients with DM.